Impacts of Ocean Acidification on Marine Biodiversity - United Nations Environment Programme World Conservation Monitoring Centre (United Nations Environment Programme-WCMC) (UNEP World Conservation Monitoring Centre (UNEP-WCMC), 2016)
UNEP-WCMC has provided technical support to the Secretariat of the Convention on Biological Diversity (CBD) to conduct a major study of more than 300 scientific literatures to synthesise the observed and predicted impacts of ocean acidification on marine biodiversity. The study, Scientific Synthesis of the Impacts of Ocean Acidification on Marine Biodiversity, describes an alarming picture of possible ecological scenarios and adverse impacts of ocean acidification for marine ecosystems, and highlights the direct link between climate change, ocean health and human well-being. The study was released by the CBD on the 14th December 2009 to mark Oceans Day and inform the climate change negotiations in Copenhagen.